Produktivitas rumput gajah (Pennisetum purpureum cv Taiwan) hasil irradiasi sinar gamma pada dosis 50 Gy - Harmini Harmini; Sajimin Sajimin; Achmad Fanindi; Ali Husni (Politeknik Negeri Jember, 2021)
The study aims to determine the productivity of elephant grass cv Taiwan (Pennisetum purpureum cv Taiwan) from gamma ray irradiation at a dose of 50 gy at five harvest in one year. The study used a randomized block design (RBD) with 3 replications, the treatment was 51 numbers clone of elephant grass (P. purpureum cv Taiwan) from gamma ray irradiation and control (without irradiation). Observations were made on each number of elephant grass irradiated on 5 plants per number, and were made on 10 plantswith a harvest interval of 2 months. The observed parameters include the number of tillers; fresh and dry leaf weight; fresh and dry stem weight, and total weight. The results showed a significant impact of gamma radiation (P<0.05) on tiller count, fresh leaf weight, dry leaf weight and fresh stem weight as well as dry stem weight and total weight. These results show that gamma radiation on elephant grass can generate diversity and increase its productivity. The best cuttings can be made on the fourth cut in clones no. 19, 1, 27, 31 and 3.